Menanamkan Nilai Kesetaraan Gender melalui Pendidikan Agama Islam - Atsila Taris Arihiyah; Yayah Khoiriyah; Siti Mutthola'ah (FKIP UNSULTRA, 2025)
Gender equality is a crucial issue in the development of modern education, including in the context of Islamic Religious Education (PAI). This literature review aims to analyze the concept of gender equality from an Islamic perspective and examine how these values ​​can be instilled through Islamic Religious Education (PAI) instruction at various levels of education. This research employed a literature review method, reviewing journal articles, books, and relevant research findings from the past five years. The results indicate that Islam, in principle, places men and women as equal beings in terms of human values, moral responsibility, and spiritual potential. Quranic verses such as Surah Al-Hujurāt: 13 and Surah An-Nahl: 97, as well as the Prophet's hadith, emphasize respect for women's dignity and justice in social relations. In practice, PAI plays a strategic role in building students' critical awareness of gender bias, providing a comprehensive understanding of the principle of justice in Islam, and fostering mutual respect between men and women. Integrating equality values ​​can be achieved through the curriculum, an inclusive pedagogical approach, teacher role models, and the use of gender-sensitive teaching materials. However, various challenges were identified, such as patriarchal culture, rigid textual interpretations, and a lack of teacher training. This study concludes that Islamic Religious Education (PAI) has great potential as a means of internalizing gender equality values, provided it is supported by a humanistic educational paradigm, moderate interpretations, and supportive institutional policies. Curriculum strengthening and teacher training are needed so that PAI can optimally contribute to realizing a gender-just society.